Factors explaining crop price developments: Time-series evidence for developing and developed countries - Katharina Raabe (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
The global hunger indices of 2008 and 2009 (Grebmer et al. 2008, 2009) point to persistently high levels of hunger and food insecurity and a worsening of the situation due to rising crop prices. At the same time, there is a lack of empirical knowledge on the demand- and supply-side determinants of crop prices. Given this situation, this paper estimates structural equation models by means of the three-stage least-squares estimator to identify the sensitivity of the price of three major crops (wheat, maize, and rice) in up to eight countries (India, China, Egypt, Thailand, Ecuador, Uruguay, the United States, and Australia) to global and country-specific crop demand and supply conditions. The evidence suggests that conclusions regarding the determinants of crop prices critically depend on the choice of crop and country. The nonexistence of a consistent and homogenous set of price determinants suggests that the stability and predictability of crop prices depends on country-specific domestic policies that target both the crop demand and supply side. The evidence also suggests that supply-side initiatives are likely to be more effective to this end.
Keywords: C32; Q11; Q19; 330; Agriculture; food prices; crop prices; simultaneous equations; three-stage least-squares; Getreidepreis; Getreidemarkt; Agrarpolitik; Nahrungsmittelpreis; Vergleich; Schätzung; Indien; China; Ägypten; Thailand; Ecuador; Uruguay; USA; Australien